Radon Concentration in the Work Atmosphere of Cement Plants in the Sulaymaniyah Area, Iraq - Hussein, Adil M.; Abdullah, Kamal O.; Faraj, Kharman A.; Hamamin, Dara F. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2018)
This work reports the radon concentration level in the work environment of cement plants (CPs) located in the Sulaymaniyah city-North of Iraq. This survey for the radon concentration is performed in 24 sectors of three different CPs including Tasluja, Mass, and Bazian. The measurements were recorded using solid state nuclear track detector (CR-39 NTDs). The radon effective dose μSv/hr correlated weakly with the gamma effective dose μSv/hr to enhance the radon concentration measuring. The detector was fixed in different places of the plants such Crusher, Correction stores, Raw Mill (Grinding Mill), Preheater (Tower), Clinker, and Cement Storage. The arithmetic mean (AM) value of radon concentration (Ca) was found to be 98 ± 9, 101 ± 10, and 125 ± 10 Bq m−3 and the arithmetic mean value of annual effective dose (E) of radon was 0.767, 0.753, and 0.962 mSv y−1 for Tasluja, Mass, and Bazian CPs, respectively. The maximum values of about 222 ± 20 Bq m−3 and 1.402 mSv y−1, respectively, in sector III (Grinding) at Bazian CP. The achieved results reveal that the maximum value of radon concentration in all sectors of the CPs is below the international standard value (300 Bq m−3) of both the World Health Organization and International Commission on Radiological Protection.